Cost-benefit analysis of a national influenza vaccination program in preventing hospitalisation costs in Australian adults aged 50–64 years old. Issue 40 (20th September 2019) - Raj, Suresh Mahendra; Chughtai, Abrar Ahmad; Sharma, Anurag; Tan, Timothy C.; MacIntyre, C. Raina
Abstract: Introduction: Influenza causes a significant burden among Australian adults aged 50–64, however, vaccine coverage rates remain suboptimal. The National Immunisation Program (NIP) currently funds influenza vaccinations in this age group only for those at high risk of influenza complications. Aims: The main aim of this study was to determine whether a strategy of expanding the government-funded vaccination program to all adults 50–64 in preventing influenza-related hospitalisations will be cost beneficial to the government. Methods: A cost-benefit analysis from a governmental perspective was performed using parameters informed by publicly available databases and published literature. Costs included cost of vaccinations and general practitioner consultation while benefits included the savings from averted respiratory and acute myocardial infarction (AMI) hospitalisations. Results: In the base-case scenario, the proposed policy would prevent 314 influenza/pneumonia, 388 other respiratory and 1482 AMI hospitalisations in a year. The government would save 8.03 million with an incremental benefit-cost ratio of 1.40. Most savings were due to averted AMI hospitalisations. In alternative scenarios cost savings ranged from saving of 31.4 million to additional cost to the government of 15.4 million, with sensitive variation in vaccine administration practices (through general practitioner or pharmacists) and vaccine effectiveness estimates. Discussion: Extension of the NIP to include adults 50–64 years of age is likely to be cost beneficial to the government, although this finding is sensitive to vaccine administration cost, which varies if provided through general practitioners or pharmacists; and to variation in vaccine effectiveness. An increased role of pharmacists in immunisation programs would likely result in cost savings in an expanded adult immunisation program.